Psychometric properties of the COVID-19 associated PTSD-Scale - Rudwan, Samer Jamil (European Scientific Journal, ESJ, 2021)
This study aimed to create a scale to measure post-traumatic stress disorder (PTSD) symptoms related to the COVID 19 crisis. Based on the available studies, the Davidson PTSD scale dimensions were used in this online survey. Accordingly, a new scale was designed based on the clinical characteristics of the symptoms of the PTSD, so questions revolved around the possible psychological PTSD symptoms associated with COVID 19. Descriptive approach was used. The study involved 423 participants from the Sultanate of Oman, of whom, 219 were male and 204 were female. Statistical analyses of the scale were conducted using reliability, criterion-related validity, as well as exploratory and confirmatory factor analysis. The factor analysis revealed three factors to which 15 items of 17 items were loaded that reflect the clinical features of PTSD symptoms. Overall, the scale showed good internal consistency and stability, with relatively good correlations between the items within the factors. The analysis of the confirmation factors led to model fit validation with 14 items, with the results showing a high degree of conformity. Accordingly, the results were discussed, and further studies suggested to further verify and confirm the scale validity.